2021
DOI: 10.1016/j.heliyon.2021.e08635
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity, health and well-being among a nationally representative population-based sample of middle-aged and older adults in India, 2017–2018

Abstract: Background This study aimed to determine the association between physical activity (PA) and health and well-being in middle-aged and older community-dwelling adults in India. Methods The cross-sectional sample consisted of 72,262 individuals (≥45 years) from the Longitudinal Ageing Study in India (LASI) Wave 1 in 2017–2018. Logistic regression, adjusted for relevant confounders, was used to predict associations between PA levels and 23 health indicators. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Functional disability was measured based on ‘Activities of Daily Living (ADL) (six items) and Instrumental ADL (IADL) (seven items)36 37’; (Cronbach alpha 0.89). The responses were ‘Yes/No’ and were dichotomised into 0 or 1, and ≥2 ADL/IADL items, as in previous studies 29 38…”
Section: Methodsmentioning
confidence: 99%
“…Functional disability was measured based on ‘Activities of Daily Living (ADL) (six items) and Instrumental ADL (IADL) (seven items)36 37’; (Cronbach alpha 0.89). The responses were ‘Yes/No’ and were dichotomised into 0 or 1, and ≥2 ADL/IADL items, as in previous studies 29 38…”
Section: Methodsmentioning
confidence: 99%
“…Historical literature suggested that physical inactivity was strongly correlated with poorer psychosomatic health in patients with schizophrenia (18). In contrast, regular physical activity significantly improved patients' insomnia symptoms and their subjective sleep quality to a consistent degree (14,35). A randomized controlled study in Germany noted that patients with regular physical activity had significantly better sleep quality than psychiatric patients with physical inactivity (36).…”
Section: Discussionmentioning
confidence: 99%
“…Strong evidence suggested that regular physical activity enhanced mental health (12) and could predict a better global and social quality of life in schizophrenic patients (13). Furthermore, higher physical activity levels were strongly related to fewer insomnia symptoms, better cognitive functioning, social functioning, and life satisfaction compared to lower levels of physical activity (14).…”
Section: Introductionmentioning
confidence: 99%
“…Depressive symptoms among middle-aged and older people are a major challenge facing current society, especially in low- and middle-income countries (LMICs). A previous national survey in LMICs showed that the prevalence of depression symptoms among middle-aged and older people aged ≥ 45 years in India, China, and Thailand was 27.6% [ 1 ], 36.7% [ 2 ] and 19.4% [ 3 ], respectively. However, the prevalence of depressive symptoms in high-income countries such as the UK and the US was 13.6% [ 4 ] and 8.7% [ 5 ], respectively.…”
Section: Introductionmentioning
confidence: 99%